Analysis of Passenger Evacuation Time During Fire on KL. Sultan Hasanuddin (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
The aim of this study is to determine the time required in the evacuation of the passengers KL. Sultan Hasanuddin when it experienced a fire based on IMO regulations. Data from the National Transportation Safety Committee (KNKT) shows that 221 shipping accidents were investigated during 2007-2023. The majority of accidents are classified as ships on fire (33 percent) with one of the biggest handling focuses on passenger ships and most of the accidents resulted in fatalities, so it is necessary to provide input and information regarding the evacuation of passengers and cadets regarding the process and time of evacuation when the ship experiences a fire. The type of research is quantitative research using pathfinder software simulation whose evacuation route is based on safety plan data fo KL. Sultan Hasanuddin. From the simulation results and analysis obtained the time required in evacuating passengers KL. Sultan Hasanuddin when experiencing a fire based on the provisions of IMO MSC.1/Circ.1238 in night conditions is 25.44 minutes and in daytime conditions 24, 43 minutes, which is faster during the day due to the distribution of passengers on the deck which reduces the density on the evacuation route. The alternative evacuation route on the main deck is 24% faster than the evacuation route planned in the Safety Plan, thus providing an opportunity for passengers to evacuate faster and avoid fire smoke.
Keywords: Evacuation; KL. Sultan Hasanuddin; IMO; Pathfinder